Hegemonic Masculinity in the Tradition of Women Proposing Marriage - Refti Handini Listyani; Natasya, Yurike; Moh Syamsi Dhuha; Erfina Dwi Rosidah; Rif’a Izza Sailurroqma (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines the hegemony of masculinity within the tradition of women proposing to men in Lembor Village, Lamongan. While this tradition seemingly grants women agency, it remains embedded within patriarchal structures that reinforce male dominance. The novelty of this research lies in its critical approach, employing Connell’s theory of hegemonic masculinity to analyze power dynamics in gender relations. Using qualitative methods, data were collected from 15 participants, including women who proposed marriage (6), male counterparts (4), family members (3), and community leaders (2). The study utilized semi-structured interviews to explore personal experiences and social perceptions, complemented by participant observations of marriage proposal rituals. Additionally, literature reviews encompassed previous ethnographic studies, gender theory, and local marriage customs to contextualize findings. Results indicate that, despite women initiating marriage proposals, major decisions including marriage approval, dowry negotiations, and wedding arrangements are still controlled by the male’s family, reinforcing gender hierarchies and positioning women in a subordinate role. Furthermore, societal perceptions stigmatize women who actively propose, as they are deemed to violate traditional femininity. While the tradition offers limited space for women’s initiative, it ultimately adapts patriarchal norms rather than dismantling them. These findings highlight how hegemonic masculinity remains deeply embedded within cultural traditions, shaping gender relations through structural dominance and symbolic power.